2011
DOI: 10.1002/cb.341
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation consumption: When feeling better is the aim

Abstract: This research explored how individuals regulate their emotions by consuming products of a hedonic nature. We introduce a new construct to the consumer research literature, emotion regulation consumption (ERC), which involves the consumption or purchase of a good or service for the purposes of alleviating, repairing, or managing an emotion in the short term. Specifically, ERC processes were examined for four discrete emotions -sadness, amusement, contentment, and fear/anxiety. Additionally, this research demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 106 publications
(95 reference statements)
3
65
0
2
Order By: Relevance
“…Despite a broad array of consumer research examining the regulation of negative emotions, the specific emotion of fear has received little attention (see Kemp and Kopp [2011] for an exception). However, within the domain of group dynamics, it has been shown that individuals cope with fear through interpersonal means (Morris et al 1976;Schachter 1959).…”
Section: Fear In Consumer Behaviormentioning
confidence: 98%
“…Despite a broad array of consumer research examining the regulation of negative emotions, the specific emotion of fear has received little attention (see Kemp and Kopp [2011] for an exception). However, within the domain of group dynamics, it has been shown that individuals cope with fear through interpersonal means (Morris et al 1976;Schachter 1959).…”
Section: Fear In Consumer Behaviormentioning
confidence: 98%
“…Hedonic shopping value is actualized through fantasy and the multisensory and emotive aspects of the shopping experience (Kemp and Kopp, 2011;Wu et al, 2015), which is based on the enjoyment and excitement of consuming hedonic products (Babin et al, 1994;Chitturi et al, 2008). In contrast, consumers' utilitarian shopping behaviour is more rational, task-related (Chitturi et al, 2008), and extrinsically motivated (i.e., the consumer expects a reward or benefit external to the system-user interaction) ( Van der Heijden, 2004), wherein satisfaction comes from accomplishing a task-the acquisition of a product, information, or both-in an efficient manner and reflects a more instrumental, goaldriven, and cognitive approach to shopping (Babin et al, 1994).…”
Section: Regulatory Focus and Hedonic Versus Utilitarian Websitesmentioning
confidence: 99%
“…For instance, people may take a hot shower when they feel lonely (Bargh & Shalev, 2012, 2014, cuddle a teddy bear when they feel afraid (Koole, Tjew A Sin, & Schneider, 2013), or treat themselves to a nice gift to lift their spirits (Kemp & Kopp, 2011). A second set of affordances thus consists of various kinds of tools and artifacts that people may recruit in emotion regulation.…”
Section: Tool Affordancesmentioning
confidence: 99%